Broadening the spectrum of ivermectin: Its effect on Trypanosoma cruzi and related trypanosomatids - Fraccaroli, Laura; Ruiz, María Daniela; Perdomo, Virginia Gabriela; Clausi, Agustina Nicole; Balcazar, Darío Emmanuel; Larocca, Luciana; Carrillo, Carolina (Frontiers in Cellular and Infection Microbiology, 2022)
Chagas disease is an endemic American parasitosis, caused by Trypanosoma cruzi. The current therapies, benznidazole (BZN) and nifurtimox (NFX) show limited efficacy and multiple side effects. Thus, there is a need to develop new trypanocidal strategies. Ivermectin (IVM) is a broad-spectrum antiparasitic drug with low human and veterinary toxicity with effects against T. brucei and Leishmania spp. Considering this and its relatively low cost, we evaluate IVM as a potential repurposed trypanocidal drug on T. cruzi and other trypanosomatids. We found that IVM affected, in a dose-dependent manner, the proliferation of T. cruzi epimastigotes as well as amastigotes and trypomastigotes survival. The Selectivity Index for amastigote stage respect to Vero cells was 12. IVM effect was also observed in Phytomonas jma 066 and Leishmania mexicana proliferation but not in Crithidia fasciculata. On epimastigote stage the IVM effect was trypanostatic at 50μM but trypanocidal at 100μM. Assays of drug combinations of IVM with BNZ or NFX showed mainly additive effects among combinations. In silico studies showed that classical structures belonging to glutamate-gated Cl− channels, the most common IVM target, are absent in kinetoplastids. However, we found in the studied trypanosomatid genomes one copy for putative IMPα and IMPβ, potential targets for IVM. The putative IMPα genes (with 76% similarity) showed conserved Armadillo domains but lacked the canonical IMPβ binding sequence.